PELATIHAN PEMBUATAN MATERI AJAR BERBASIS ANDROID BAGI DOSEN UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Nine Febrie Novitasari; Sufil Lailiyah (INTEGRITAS : Jurnal Pengabdian, 2017)
This event was held as one of efforts to solve the problem of limited and unintersting teaching materials in Abdurachman Saleh University. Being concerned with this, with the widely used of android-based gadgets by both the lecturers and the students, we held a training for the lecturers to provide skills to develop their android-based materials that later could be sold in play store. To propose an interactive teaching material, the lecturers were given a one-day training of how to develop android-based teaching materials. During the training, the lecturers were given chances to discuss with the trainer on the problems they had to find the best solutions. The lecturers were also motivated to develop an interesting and worth-selling product in the form of teaching materials. The outputs expected from the training are: (1) developing skills for the lecturers to create interesting and interactive teaching materials, (2) developing skills for the lecturers to create innovative teaching materials, which is android-based teaching matrials, (3) creating android-based teaching materials, (4) developing entrepreneurship for the lecturers, (5) finding solutions for limited and uninteresting materials, (6) providing access to interesting and interactive materials.